Recommendations on Classifying Didactic Games and Using Them in Eliminating Speech Deficiencies in Children - Soliyev Ilhom Sobirjonovich; Fozilova Dilnoza Mukhtorjon kizi (Zien Journals, 2023)
In this article, as children grow and mature, their speech also develops, research works have been conducted in various directions in order to eliminate the speech deficits of children of preschool age, to what extent games influence children's speech activity. information about testing through different games is given. Speech disorders have a negative impact on the formation of a child's personality and the development of cognitive activity. It is known that in order to communicate with disabled children, a pedagogue must have very strong pedagogical skills
Keywords: speech; education; defect; pedagogical communication